Mesa principal de una reunión. (UNED, 2023)
Aparecen de izquierda a derecha Carlos Luis Fallas Monge, el Rector - Chester Zelaya Goodman, Marco Vinicio Álvarez Amador, Luis Edgardo Ramírez, José Joaquín Villegas Gijalba, Marcelo Blanc Macías,